The evaluation of surgical reconstruction for intermittent claudication by the Walking Impairment Questionnaire - Nakashima,Masaya (2010)
BACKGROUND: No standards reflecting the quality of life (QOL) and activity of daily living (ADL) in postoperative clinical course have been validated in the area of vascular disease. The Walking Impairment Questionnaire (WIQ) is a disease-specific questionnaire that evaluates patients with intermittent claudication due to arteriosclerosis obliterans (ASO). The WIQ uses four subscales: pain severity, walking distance, walking speed, and stair climbing while walking. OBJECTIVE: To evaluate the correlation between postoperative arterial blood flow and the Japanese edition of the WIQ. METHODS: Thirty-one patients (47 limbs) with intermittent claudication who had been subjected to lower limb surgical arterial reconstruction were assessed by WIQ, and compared with Ankle-Brachial Pressure Index (ABPI) and angiography. RESULTS: A significant increase in the WIQ score was identified in walking pain (26 versus 89.5, p<0.001), walking distance (13.1 versus 83.3, p<0.001), walking speed (10 versus 46, p<0.001), and stair climbing (6.2 versus 79, p<0.001). The correlation coefficient between the increase in postoperative ABPI and the WIQ score was R²=0.1889, which shows weak correlation. The correlation between blood flow obstruction due to the postoperative bypass that was scored by angiography and WIQ score was R²=0.3894, which shows moderate correlation. CONCLUSION: An improvement in the Japanese edition of the WIQ score was correlated not only with the patients' QOL after bypass revascularization but also with the rate of increase of postoperative ABPI and image findings, such as the postoperative angiography.